Particularidades e similaridades do registro Rupestre da fazenda mundo novo em Canindé de São Francisco - SE - Souza, Vanessa Santos (2013)
Xingó´s Region located between the states of Alagoas, Bahia and Sergipe has a big archeological heritage and since the 80´s researches have been made in order to enrich the data related to the local pre-historical man. From these initial researches, 15 sites were studied with rock art between the states of Alagoas and Sergipe, where it was found out that the sites show a theme particularity among the sites with difficult insertion to the rupestrian traditions. However, through new diggings, a great number of sites with rupestrian records were identified. On this particular research, the sites of the uptown region of Xingó were classified, the plateau region, so it was observed that there are in the area some groups of rock art, among these ones, the one which is in Sergipe territory, located at Mundo Novo Farm, in the county of Canindé de São Francisco. From these initial researches, some questions came up in relation to the particularity and the peculiar identity rock art in Xingó. The Mundo Novo Farm, object of study of this research, presents a repertory with themes in common with the rest of the region, the same way that also shows particular and unique elements, what suggests that the area of study may have been a place of continuity and cultural consolidation.